Pressing Issues of Forensic and Expert Support for the Investigation of Iatrogenic Crimes - M. V. Tuzlukova (Теория и практика судебной экспертизы, 2020)
There has been an increase in the relevance of forensic and expert support for investigating the negligent harm caused by health workers to patients' health, often resulting in death. Such actions (inaction) of medical workers are identified as a specific category of “iatrogenic crimes”. The forensic characteristic of iatrogenic crimes has some distinct features, including their subject, distinctiveness of the circumstances that occur during diagnostic, treatment, and rehabilitation procedures, as well as the ways of hiding the traces of a crime. To improve the quality of the investigation of iatrogenic crimes, the author proposes to create a forensic information network, substantiates the need to ensure the possibility of remote consultations for investigators with highly qualified medical specialists using telemedicine technologies, and to conduct thorough preparation for the appointment of forensic examinations. It is recommended that the concluding documents of every investigation and trial of iatrogenic crimes include a more detailed presentation of the progress and results of expert opinions' assessment.